Pola Kepekaan Bakteri Terhadap Antibiotik pada Pasien Rhinosinusitis - Hasna Laili Jovita (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Rhinosinusitis is an inflammation affecting the nose and paranasal sinuses. One of the medical treatments is with antibiotics. The irrational use of antibiotics creates problems, namely bacterial resistance and complications. Objective: To determine the pattern of bacterial sensitivity to antibiotivs in rhinosinusitis patient. Methods: Using literature studies by examining various national and international journals, comparing and combining the findings of the research presented in the article. Result: The determination of antibiotics as medical treatment in rhinosinusitis must be appropriate and provide maximum effectiveness for healing. Conclusion: There are several result of the pattern of bacterial sensitivity to antibiotics according to the bacteria that cause rhinosinusitis.